Analisis Karotenoid dan Glukosa pada Produksi Serbuk Jahe Merah (Zingiber officinale Rosc. var Rubrum) terhadap Variasi Suhu dan Kadar Gula - Nuramalia, Rachma Nisa; Sari, Dessy Agustina (Universitas Harapan Medan, 2024)
This study aims to analyze total carotenoids and total sugar in red ginger powder products by involving variations in sugar content and process temperature. The process of making red ginger powder utilizes an evaporation process with rock sugar as a crystallization agent to help the crystallization process. The raw material is red ginger as the main material, both fresh and pulp. Then, the variables during the study were operating temperature (80 and 90oC) and sugar content (60 and 100%). The parameters analyzed were total carotenoids and total sugar in the red ginger powder samples. The results of the total carotenoid analysis showed that the treatment of red ginger with a temperature of 90oC and 60% rock sugar content provided optimum conditions both in terms of fresh raw materials and pulp. This result was also achieved in red ginger powder and ready-to-consume beverage products, which ranged from 11.70 to 16.23%. Furthermore, the best total glucose analysis results were at the same temperature as the highest carotenoid values. Meanwhile, the highest sugar content (100%) was able to provide higher total glucose than the 60% contribution of rock sugar in both raw material conditions and the form of processed red ginger products.